A cationic gold complex cleaves BArF24 - Weber, Simone G.; Zahner, David; Rominger, Frank; Straub, Bernd Franz (Chemical communications, 2012)
A sterically shielded cationic NHC gold complex IPr**Au-BArF24 without solvent coordination has been prepared in situ in CH2Cl2. The monovalent transition metal electrophile, a “soft proton”, heterolytically activates the C-B bond of the weakly coordinating counterion tetrakis[3,5-bis(trifluoromethyl)phenyl]borate at room temperature.
Gesehen am 03.04.2019